Quantifying the benefits of wetland restoration under projected sea level rise - Familkhalili, Ramin; Davis, Jenny; Currin, Carolyn A.; Heppe, Madison E.; Cohen, Susan (Frontiers in Marine Science, 2023)
The capacity of vegetated coastal habitats to mitigate erosion and build elevation in response to sea-level rise (SLR) has led to growing interest in their application as Nature Based Solutions (NBS) for shoreline protection. However, a significant uncertainty in the performance of NBS is how these features will respond to future rates of SLR. In this study, we applied the Sea Level Affecting Marshes Model (SLAMM) to a fringing shoreline wetland complex that is directly adjacent to the primary runway of a regional airport in coastal North Carolina, US. The SLAMM model was run at high spatial resolution (1 m cell size) to investigate the effects of projected SLR by 2100 on the wetland communities and to estimate the potential benefits of a proposed NBS project involving the use of dredged sediment to increase wetland surface elevation. Modeling future habitat extent under three SLR scenarios (i.e., intermediate, intermediate-high, and high) with no land modification reveals a consistent pattern of salt marsh expanding into fresh marsh, salt marsh transitioning to higher elevations, and substantially larger overall extents of intertidal and subtidal habitats within the project footprint at relatively high rates of SLR. Simulations that include the NBS indicate changes in the composition of wetland types over time compared with the no-action scenario. Model results help to better understand the long-term behavior of fringing coastal wetlands and the efficacy of their use as part of coastal resilience strategies.